Corrigendum to “Preparation and Characterization of Novel Poly (Lactic Acid)/Calcium Oxide Nanocomposites by Electrospinning as a Potential Scaffold for Bone Tissue Engineering” [Biomater. Adv. 2023 153 213578 (Biomaterials Advances 2023 153 s2772950823003011 (10.1016/J.Bioadv.2023.213578)) - Zapata-Ramirez, P; Canales-Arévalo, D (Elsevier Ltd, 2023)
The authors regret <insert corrigendum text>. In the article, is necessary to add a new affiliation, specifically for the co-author Carlos H. Valencia-Llano. The new affiliation is: Grupo Biomateriales Dentales, Escuela de Odontología, Universidad del Valle, Calle 4B # 36-00, Cali 76001, Colombia Considering this modification, the new section of authors and affiliation would be: Daniel Canales1,2⁎, Dominique Moyano1, Fabian Alvarez2, Carlos David Grande-Tovar3, Carlos H. Valencia-Llano4, Laura Peponi5, Aldo R. Boccaccini6,7, Paula A. Zapata 1* 1Grupo Polímeros, Departamento de Ciencias del Ambiente, Facultad de Química y Biología, Universidad de Santiago de Chile, USACH, Casilla 40, Correo 33, Santiago, Chile. (daniel.canales@usach.cl)(paula.zapata@usach.cl) 2Laboratorio de biomecánica y biomateriales, Departamento de ingeniería mecánica, Facultad de ingeniería, Universidad de Santiago de Chile, USACH, Santiago, Chile 3Research Group of Fotoquímica y Fotobiología, Universidad del Atlántico, Carrera 30 Número 8-49, Puerto Colombia 081008, Colombia 4Grupo Biomateriales Dentales, Escuela de Odontología, Universidad del Valle, Calle 4B # 36-00, Cali 76001, Colombia 5Instituto de Ciencia y Tecnología de Polímeros (ICTP-CSIC), Madrid, España 6Department of Materials Science and Engineering, Institute of Biomaterials, Friedrich- Alexander-University Erlangen-Nuremberg, Erlangen, Germany 7Bavarian Polymer Institute, 91058Erlangen, Germany The authors would like to apologise for any inconvenience caused. © 2023 Elsevier B.V.